Ресурсний підхід у підготовці майбутніх учителів до інноваційної діяльності - Микитюк, Сергій Олександрович (НТУ "ХПІ", 2011)
The article shows the value of resource approach in preparing future teachers to innovative activity. The main ideas of resource approach are presented in the article. Also it is stated that resource approach changes the strategy of educational establishment, promotes adjustment of future teachers training content with the demands of modern society, optimizes tools, forms and methods of training.
Keywords: ресурсний підхід; інновації; вчитель; особистість